Islam, Nationalism and Democracy: A Dialoguewith Dr. Anwar Haryono - Prasetyo, Hendro (Studia Islamika, 1995)
This article contains an interview on Islam, Nationalism, and Democracy with Dr. Anwar Haryono.We would like to discuss the situation of Islam and Muslim in New Order Indonesia. To be more specific perhaps, we would like to begin with something rather controversial i.e the coming to power of the New Order goverment. This goverment has set up new policies on Islam, which are different from such policies employed by the previous goverment. REsponding to New Order policies, some Muslim prefer to adobt the so-called "Cultural Islamic Movement", such as that promoted by Nurcholis Madjid, rather than the "Political Islamic Movement" as in the Old Order period. Nontheless, the New Order goverment stil gives opportunities to Muslims to pursue their political aspiration through the PPP (Partai Persatuan Pembangunan - the United Development Party). Before discussing the more recent situation, it would be best if you could sketch out the Muslim position in the early decades of independent Indonesia.DOI: 10.15408/sdi.v2i1.846